2008
DOI: 10.1007/s00467-008-0832-z
|View full text |Cite
|
Sign up to set email alerts
|

Disparate outcomes in pediatric peritoneal dialysis patients by gender/race in the End-Stage Renal Disease Clinical Performance Measures project

Abstract: Associations between achievement of adult Kidney Disease Outcomes Quality Initiative (KDOQI) targets for hemoglobin, adequacy and albumin, and race and gender were determined for pediatric peritoneal dialysis patients from the End-Stage Renal Disease (ESRD) Clinical Performance Measures (CPM) project for the period October 2004-March 2005. Fifty-six percent (427/761) of patients were male. Sixty-six percent (500/761) of patients were White. There were no differences in achievement of targets for adults by gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
2
1
Order By: Relevance
“…Anemia may adversely affect hemodynamics in CRF patients and thus impair dialysis adequacy. 36,37 In our study, no statistically significant relationship was found between hemoglobin levels and dialysis adequacy.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Anemia may adversely affect hemodynamics in CRF patients and thus impair dialysis adequacy. 36,37 In our study, no statistically significant relationship was found between hemoglobin levels and dialysis adequacy.…”
Section: Discussioncontrasting
confidence: 70%
“…With peritoneal dialysis, albumin and protein are lost. 36,37 Albumin level is an important parameter showing dialysis adequacy. In our study, no statistically significant relationship was found between albumin levels and parameters of dialysis adequacy.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship is also seen in adult hemodialysis patients (21). Atkinson et al showed that African-American children on peritoneal dialysis were less likely to achieve hemoglobin values of 11 g/dL or greater when compared to white children (22). Given the presence of a greater disparity in mortality in children who do not achieve target hemoglobin values, further work is necessary to address the etiologies in disparate hemoglobin values.…”
Section: Discussionmentioning
confidence: 99%